2019
DOI: 10.3390/inventions4020030
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Control Synchronization of a Novel Memristive Chaotic System for Secure Communication Applications

Abstract: In this paper, a new memristive chaotic system is designed, analyzed, tested, and proposed. An adaptive control synchronization mechanism for both master and slave chaotic systems is also designed. The adaptive control law of this mechanism is derived based on the Lyapunov theory. A single parameter in the slave system has been assumed to be unknown. As the parameters of the master and slave are asymptotically matched, the unknown slave parameters will be identified according to the master’s parameters. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It is proved that a symmetric system or a conditionally symmetric system can be constructed by using offset boosting. (2) e dynamic characteristics of the new system generated by scale change are the same as that of the original system, but a nonbifurcation parameter can be formed to adjust the amplitude and frequency of system (3). e simulation circuit verifies the amplitude modulation characteristics of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proved that a symmetric system or a conditionally symmetric system can be constructed by using offset boosting. (2) e dynamic characteristics of the new system generated by scale change are the same as that of the original system, but a nonbifurcation parameter can be formed to adjust the amplitude and frequency of system (3). e simulation circuit verifies the amplitude modulation characteristics of the system.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, HP laboratory released a TiO 2 charged memristor [1], declaring that a memristor was found. A large number of research studies on memristor models and typical chaotic systems have been published, making the memristor widely studied in secure communication [2,3], cryptography [4,5], image encryption [6,7], associative memory [8,9], voice encryption [10], and recognition and sequencing application [11]. Wang et al [12] reported a special bursting behavior previously unobserved in third-order autonomous memristive circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The synchronization between two systems can be achieved when the trajectories of two systems are matched [29][30][31]. In chaos systems, the synchronization mechanism plays a significant role in constructing secure communication schemes [32][33][34]. It can occur between two chaotic systems; one is a master and the driven one is a slave [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The work on applications of chaotic synchronization in secure communication has grown dramatically in recent years [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Developing control systems for synchronization of various chaotic systems has been one of the main focuses of prior works, aiming to improve security in communication.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of utilizing adaptive control for synchronization is proposed in [ 32 ]. The master and slave chaos systems discussed in this work are of the memristor type.…”
Section: Introductionmentioning
confidence: 99%